Method for accurately controlling oxygen content of low-carbon low-silicon high-sulfur steel
Through the precise control of converter smelting, LF refining and continuous casting processes, the problem of difficult control of oxygen content and silicon content in smelting high-sulfur steel is solved, and the precise control of oxygen content and cutting performance of low-carbon, low-silicon, high-sulfur steel is achieved. Meet the needs of mid-to-high-end users.
Patent Information
- Application Number
- CN202411211058.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The prior art is difficult to accurately control the oxygen content in the steel when smelting high-sulfur steel, resulting in unstable cutting performance and tool wear, and poor control of silicon content in low-carbon high-sulfur steel, affecting the needs of mid-to-high-end users.
Through precise control of converter smelting, LF refining and continuous casting processes, step-by-step weak deoxygenation process, environmentally friendly aluminum-based reducing agent and light pressure technology, the oxygen content and sulfide form of the molten steel are accurately controlled, and the content of silicon and aluminum is reduced. Ensure excellent cutting performance.
The precise control of the oxygen content of low-carbon, low-silicon, high-sulfur steel is achieved, and the morphology and cutting performance of sulfide inclusions is improved, the content of silicon and aluminum is reduced, the needs of mid-to-high-end users are met, and the production costs and environmental impact are reduced.
Smart Images

Figure CN119120837A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of iron and steel metallurgy, and in particular relates to a method for accurately controlling the oxygen content of low-carbon, low-silicon and high-sulfur steel. Background Art
[0002] Sulfur is one of the main impurity elements in general steel grades, which can cause problems such as "hot brittleness" and reduced toughness of steel. However, adding a certain amount of sulfur to steel can form MnS inclusions that can cut off the continuity of the steel matrix, acting as a stress concentration source during the processing of steel parts, improving the cutting performance of steel and reducing tool wear.
[0003] There are three main types of manganese sulfide morphologies in low-carbon high-sulfur steel: Type I MnS is spherical or spindle-shaped, precipitated with oxides as the core; Type II MnS is fan-shaped or chain-shaped, spontaneously nucleated and grown; Type III MnS is polyhedral, spontaneously nucleated and grown. Type I MnS inclusions contain oxide cores, are small in size, are not easily deformed during rolling, and are not easily stretched into long strips. The spherical or spindle-shaped morphology can effectively cut off the steel matrix and improve the cutting chip breaking performance; Type II and III MnS are irregularly distributed in chain, mesh or angular shapes, spontaneously nucleated and grown, are large in size, and are single-phase MnS that are easily deformed. They are easily deformed and stretched into long strips during rolling, which is not conducive to cutting performance.
[0004] The oxygen content of molten steel is one of the key elements that affect the morphology of MnS. A certain oxygen content is conducive to increasing the nucleation particles of oxides such as FeO and MnO, reducing the average diameter and aspect ratio of MnS inclusions, increasing the proportion of type I composite MnS inclusions, and improving the cutting performance of medium and high sulfur steels. The document "Xia Yunjin, Wang Fuming, Wang Jinlong, et al., Effect of oxygen content on the formation behavior of sulfides in free-cutting steels, Journal of Beijing University of Science and Technology, Vol. 32, No. 10" discloses that "when the oxygen content is as high as 0.022%, a large amount of MnO-based low-melting liquid oxides are formed at the beginning of solidification, which promotes the transformation of the formation mode of MnS from eutectic form to eutectic form, forming type I MnS. At first, oxygen-rich liquid inclusions are formed, and the final precipitation is mainly single-phase MnS. When the oxygen content is below 0.01%, the MnO-based low-melting liquid oxides formed at the beginning of solidification are less, and most of the MnS is precipitated in the form of eutectic in the supersaturated state at the end of solidification, forming type II MnS." It can be seen that, under the premise of not affecting the cleanliness of the molten steel, appropriately increasing the oxygen content in the steel is beneficial to the control of MnS inclusions, but too high an oxygen content is prone to produce surface defects such as subcutaneous bubbles and scarring on the ingot surface. During the rolling process, the metal surface of the matrix is partially disconnected from the matrix to produce a warping defect. Although the document discloses the effect of oxygen content on the sulfide formation behavior in free-cutting steel, it does not disclose how to accurately control the oxygen content in the steel.
[0005] Chinese patent CN 115386800 A discloses a low-carbon, high-manganese-sulfur, environmentally friendly free-cutting steel and its manufacturing method, wherein aluminum iron, manganese iron and sulfur iron are added during the steel-making process for deoxidation and alloying, ferrosilicon and aluminum are used for refining to deoxidize the molten steel, and pre-melted wollastonite and lime are used for slag making. In this patent, the slag surface is not deoxidized, the silicon content of the molten steel is high, and the oxygen content of the molten steel fluctuates greatly, which is not conducive to the precise control of the total oxygen content of the ingot, and is likely to have an adverse effect on the cutting stability of the low-carbon, high-sulfur steel and the wear of the tool;
[0006] Chinese patent CN111286580 A discloses a low-carbon tellurium-containing high-sulfur free-cutting steel ingot and its production method, wherein the molten steel is pre-deoxidized by tapping silicon-manganese alloy and alloy, and the molten steel is oxygen-controlled by adding ferrosilicon powder or iron oxide scale during the LF refining process, and silicon-manganese, ferrosilicon and other silicon-containing raw materials are used for oxygen control. This method easily causes excessive silicon in the molten steel, and the inclusions are modified by adding tellurium elements, which has a certain effect on the cutting performance, but the addition of tellurium elements is difficult and costly, which is not conducive to stable mass production.
[0007] Chinese patent CN 117403147 A discloses a high-oxygen and high-sulfur easy-to-cut steel 1215MS and its oxygen-controlled LF smelting method. In the steel-making process, aluminum iron, low-carbon ferromanganese and ferrosulfur are used for deoxidation and alloying, and silicon carbide and calcium carbide are used for slag surface deoxidation in refining. Silicon carbide is easy to increase silicon and carbon in molten steel. The silicon content of molten steel is high, and it needs to be tapped through a converter with low carbon. The molten steel has strong oxidizability and high deoxidation cost, which cannot meet the low silicon content requirements of mid- and high-end users.
[0008] It can be seen that the above-mentioned existing technologies do not pay special attention to the control of silicon content in steel when smelting high-sulfur steel. Low-carbon high-sulfur steel is a weakly deoxidized steel due to the high oxygen content in molten steel. Since elements such as silicon and aluminum easily react with oxygen to form a large amount of high-melting-point hard inclusions such as silicates and alumina, it will cause tool wear during the cutting process. Mid- to high-end customers hope that the silicon and aluminum content in steel is as low as possible, and they also have strict requirements on the silicon and aluminum content in steel. Summary of the invention
[0009] In order to solve the above technical problems, the present invention provides a method for accurately controlling the oxygen content of low-carbon, low-silicon, high-sulfur steel. According to the characteristics of low-carbon, low-silicon, high-sulfur steel, the converter steelmaking, LF refining and continuous casting production processes are controlled to solve the problem of large fluctuations in oxygen content control during the smelting process, and accurate control of the oxygen content of molten steel is achieved, so as to obtain castings with good sulfide inclusion morphology, good surface quality and excellent cutting performance.
[0010] The technical solution adopted by the present invention is as follows:
[0011] The present invention provides a method for accurately controlling the oxygen content of low-carbon, low-silicon and high-sulfur steel, comprising the following steps:
[0012] a. Converter smelting: put in molten iron, desulfurized slag and scrap steel for smelting; the basicity of converter final slag is controlled at 2.0-2.5; phosphorus and sulfur are not removed;
[0013] b. Carbon is retained and steel is tapped at the end of the converter, and argon is blown from the bottom for strong stirring;
[0014] c. The converter tapping process adopts a step-by-step weak deoxidation process. When the steel is tapped 1 / 2, low-carbon ferromanganese with a mass percentage of C ≤ 0.2%, high-sulfur ferrosulphur and ferrophosphorus alloy with a mass percentage of S of 50-55% are added in sequence. When the steel is tapped 3 / 4, lime and wollastonite are added. The slag is blocked by a slide plate to control the slag amount of the converter to ≤ 3kg / t.
[0015] d. Temperature measurement and oxygen determination at the argon blowing station. The dissolved oxygen content w[O] is determined by the argon blowing station. Ar Results: Precise feeding of aluminum wire. After feeding aluminum wire, the dissolved oxygen content of molten steel was controlled to be 30-80ppm. The feeding amount of aluminum wire was l Al The calculation method is shown in Formula 1: Formula 1 Among them, m st is the weight of molten steel, in t; η is the empirical parameter of aluminum wire deoxidation efficiency, when the converter end point C≥0.060%, η is 1.15~1.25; when the converter end point C<0.060%, η is 1.25~1.45; ρ Al is the density of aluminum, in kg / m 3 ; d is the diameter of the aluminum wire, in m; w Al is the mass percentage of aluminum in the aluminum wire, %; l Al The unit is m; w[O] Ar The unit is ppm;
[0016] e. The LF station is heated, and lime, raw dolomite and wollastonite are added in batches during the heating process;
[0017] f. After the heating is completed, an aluminum-based reducing agent is added to diffuse and deoxidize the slag surface, and lime and wollastonite are added to make slag;
[0018] g. After slag making, alloy fine-tuning, aluminum wire feeding or iron oxide scale addition on the slag surface are performed to control the final dissolved oxygen content of the molten steel to 45-65ppm;
[0019] h. LF is heated up twice. After the heating is completed, pure calcium cored wire is fed in to denature the sulfide inclusions. After the wire is fed, it is soft blown out of the station;
[0020] i. Continuous casting: The ingot after continuous casting is lightly pressed down;
[0021] The weight percentages of carbon, silicon and sulfur in the low-carbon, low-silicon and high-sulfur steel are respectively: C≤0.090%, Si≤0.010%, and S 0.30-0.50%.
[0022] In step a, the mass percentage of molten iron is 83-93%, the mass percentage of desulfurized slag iron is 2%-6%, and the rest is scrap steel; the S content at the converter end point is 0.030-0.060%, and the P content is 0.035-0.045%.
[0023] In step a, in the desulfurized slag iron, the mass percentage of iron is ≥50%, and the mass percentage of sulfur is 1.5-2.5%.
[0024] Furthermore, the mass percentage of T·Fe in the converter final slag is 12-15%.
[0025] In step b, the mass percentage of carbon at the converter end point is 0.060% to 0.080%, the mass percentage of oxygen at the converter end point is 300 to 400 ppm, the end point temperature is 1620 to 1660°C; the argon flow rate at the converter end point is 0.10 to 0.12 Nm 3 / min·t, stirring for 1.5~2.5min. Carbon is retained at the end of the converter to reduce the oxidation of the converter, and strong stirring is used by large flow bottom blowing to promote carbon-oxygen reaction and reduce the oxygen content of the primary steel water.
[0026] In step c, the addition amounts of low carbon ferromanganese, high sulfur ferrosulfur and ferrophosphorus alloy are 17.5±0.2kg / t steel, 22.3*(w[S] CC -w[S] BOF )±0.05kg / t steel, 39.7*(w[P] CC -w[P] BOF )±0.05kg / t steel, where w[S] CC , w[P] CC are the target values of the mass percentage of sulfur and phosphorus in the finished product, w[S] BOF , w[P] BOF They are the mass percentage of sulfur and phosphorus at the converter end point respectively; the added amounts of lime and wollastonite are 3.0-3.5kg / t steel and 1.5-2.0kg / t steel respectively.
[0027] In step c, the mass percentage of each component in low-carbon ferromanganese is: Mn 85-90%, C≤0.2%, Si≤0.5%; the mass percentage of each component in high-sulfur ferrosulphur is: S 50-55%, C≤0.1%, Si≤0.5%; the mass percentage of each component in ferrophosphorus is: P 26-30%, C≤0.1%, Si≤0.5%.
[0028] In step d, the aluminum wire has an Al content of ≥99.5% and a diameter of 9.5 to 10.5 mm.
[0029] In step e, the added amounts of lime, raw dolomite and wollastonite are 0.6-1.6 kg / t steel, 0.8-1.2 kg / t steel and 1.0-2.0 kg / t steel respectively, which are added in 4-5 batches; the arc energy is utilized to fully slag, and the raw dolomite MgCO3=MgO+CO2 decomposes to play the role of foaming agent and furnace protection agent; during the heating process, the arc gear is adjusted to match the submerged arc slag thickness to optimize the arc submerged arc efficiency.
[0030] Furthermore, the lime has a CaO content of ≥90%, the raw dolomite has a MgCO3 content of ≥40%, and the wollastonite has a SiO2 content of ≥45%.
[0031] In step f, a total amount of 0.6-1.0 kg / t steel of an environmentally friendly aluminum-based reducing agent, 0.2-0.4 kg / t steel of lime and 0.3-0.8 kg / t steel of wollastonite are added in small batches of 3-5 batches; the target composition of the refined slag is as follows by mass percentage: CaO 43-48%, SiO2 22-27%, Al2O3 14-16%, MgO 6-8%, T·Fe+MnO 6-10%, and the basicity CaO / SiO2 is 1.6-2.2; in the environmentally friendly aluminum-based reducing agent, the metal Al content is 18-22%, the Al2O3 content is 20-30%, the CaO content is 25-45%, the SiO2 content is ≤5%, the particle size is 5-30 mm, and the density is 2.3-2.7 kg / cm 3 During the slag making process, environmentally friendly aluminum-based reducing agents are added in small batches and multiple batches to diffuse deoxidize the slag surface, and lime and wollastonite are used to accurately control the composition and basicity of the refined slag, promoting the rapid equilibrium of oxygen between the slag and molten steel.
[0032] In step g, feeding 0.075 m / t steel of aluminum wire can reduce 10 ppm of dissolved oxygen; adding 0.227 kg / t steel of iron oxide scale to the slag surface can increase 10 ppm of dissolved oxygen.
[0033] In step h, the sulfide morphology and composition are determined by the parameter of the modification reaction degree γ Ca Control, degree of denaturation γ Ca The calculation method is shown in Formula 2:
[0034] Formula 2 Wherein, w[Ca] is the percentage of calcium in molten steel, in %; w[O] is the percentage of dissolved oxygen in molten steel, in %; w[S] is the percentage of sulfur in molten steel, in %; γ Ca The control range is 0.2~0.4; soft blowing takes 10~15 minutes to exit the station after feeding the line.
[0035] Furthermore, the solid pure calcium cored wire length l is fed CaThe relationship with the percentage of calcium in molten steel w[Ca] is shown in Formula 3: Among them, l Ca is the length of solid pure calcium cored wire, in m; m st is the weight of molten steel, in t; m Ca is the calcium core weight per meter, in g / m; α Ca is the percentage of electrolytic calcium in the calcium core, %; η Ca The calcium wire recovery rate is 20% to 30%. The percentage of electrolytic calcium in the calcium core of the solid pure calcium cored wire is ≥97%, the calcium-iron ratio Ca / Fe is ≥0.22, and the calcium core weight is ≥55g / m.
[0036] In step i, the total soft pressing amount is 10-20 mm, and the soft pressing devices 2, 3, 4, 5, and 6 are controlled to have a pressing amount of 1-3 mm, 2-4 mm, 3-5 mm, 3-5 mm, and 1-3 mm, respectively. The soft pressing technology for the ingot is adopted to squeeze out the bubble oxygen adsorbed on the surface of the ingot, and the pressing amount is accurately controlled to obtain the ingot with good surface quality and small sulfur segregation.
[0037] The low-carbon, low-silicon and high-sulfur steel includes the following chemical components in weight percentage: C≤0.090%, Si≤0.010%, S 0.30-0.50%, P: 0.040-0.080%, T·[O]0.010%-0.015%, dissolved [O]0.0040%-0.0070%, Alt≤0.0050%, Mn / S 3-5, and the rest is Fe and unavoidable impurities.
[0038] The method for accurately controlling the oxygen content of low-carbon, low-silicon, high-sulfur steel provided by the present invention realizes the accurate control of the oxygen content at the end point of the refined molten steel of low-carbon, low-silicon, high-sulfur steel through the above process, and denatures the sulfides according to the oxygen content and lightly presses the ingot to remove the bubbling oxygen on the surface of the ingot, thereby promoting the formation of spindle-shaped Class I MnS inclusions in the form of oxides as nuclei during the solidification process of the molten steel, thereby obtaining ingots with good surface quality, small sulfur segregation, good sulfide inclusion morphology, and excellent cutting performance.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1) According to the characteristics of low-carbon, low-silicon, high-sulfur steel, sulfur and phosphorus are beneficial alloying elements of the steel. By adding part of the desulfurized slag iron to the converter, smelting with less slag, without removing sulfur and phosphorus, the primary molten steel with high sulfur and phosphorus content is obtained, which reduces the cost of ferrosulfur and ferrophosphorus alloys; on the other hand, the metallic iron and slag in the desulfurized slag iron can be recovered, reducing the cost of converter steel materials and slag materials, while reducing the cost of desulfurized slag iron treatment and solid waste stacking problems, which is beneficial to environmental protection;
[0041] 2) According to the characteristics of low-carbon, low-silicon and high-sulfur steel, a precise oxygen control process is designed for the whole process. Carbon is retained at the end of the converter to reduce the oxygen content at the end. During the steel-making process, the amount of slag is strictly controlled, and a step-by-step weak deoxidation process is adopted. The argon station accurately feeds aluminum wire according to the oxygen determination results and the end oxidizability to control the oxygen content of the molten steel at the station. LF refining uses an environmentally friendly aluminum-based reducing agent to perform rapid diffusion deoxidation on the slag surface to achieve a balanced oxygen content between the slag and the molten steel. Aluminum wire is fed or iron oxide is added to the slag surface to accurately control the dissolved oxygen content of the molten steel at the end of LF refining. According to the sulfur and oxygen content, the sulfide is denatured to control the sulfide form and composition.
[0042] 3) According to the characteristics of low-carbon, low-silicon and high-sulfur steel, the ingot light reduction technology is adopted to accurately control the reduction amount, squeeze out the bubbling oxygen adsorbed on the surface of the ingot during the solidification process, obtain high-quality ingots with good surface quality and small sulfur segregation, and improve the cutting performance of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 These are low-magnification photos of the transverse and longitudinal sections of the ingot of Example 1, wherein the left picture is a cross section and the right picture is a longitudinal section;
[0044] Figure 2 This is the metallographic diagram of sulfide inclusions in the cross section of the wire rod in Example 1. DETAILED DESCRIPTION
[0045] The present invention is described in detail below with reference to the embodiments.
[0046] The desulfurized slag iron used in each embodiment and comparative example is from the same batch. In the desulfurized slag iron, the mass percentage of iron is ≥50%, and the mass percentage of sulfur is 1.5-2.5%.
[0047] The low carbon ferromanganese, high sulfur ferrosulfur, ferrophosphorus, aluminum wire and other alloys used in the embodiments and comparative examples are all from the same batch, wherein the mass percentage of each component in the low carbon ferromanganese is: Mn: 85-90%, C≤0.2%, Si≤0.5%; the mass percentage of each component in the high sulfur ferrosulfur is: S: 50-55%, C≤0.1%, Si≤0.5%; the mass percentage of each component in the ferrophosphorus is: P: 26-30%, C≤0.1%, Si≤0.5%.
[0048] The lime, raw dolomite and wollastonite used in the embodiments and comparative examples are all from the same batch, wherein the CaO content in the lime is ≥90%, the MgCO3 content in the raw dolomite is ≥40%, and the SiO2 content in the wollastonite is ≥45%.
[0049] The environmentally friendly aluminum-based reducing agents used in the embodiments and comparative examples are all from the same batch. In the environmentally friendly aluminum-based reducing agent, the metal Al content is 18-22%, the Al2O3 content is 20-30%, the CaO content is 25-45%, the SiO2 content is ≤5%, the particle size is 5-30 mm, and the density is 2.3-2.7 kg / cm 3 .
[0050] The solid pure calcium cored wires used in the embodiments and comparative examples are all from the same batch, with an electrolytic calcium content of 99%, a calcium-iron ratio of Ca / Fe≥0.22, and a calcium core weight of 57 g / m.
[0051] The density of the aluminum wire used in each embodiment and comparative example is 2.7 kg / cm 3 , diameter is 10mm, Al content is 99.7%.
[0052] The aluminum iron and silicon carbide used in the comparative example are from the same batch, the mass percentage of Al in the aluminum iron is ≥40%, and the particle size is 10-30 mm; the mass percentage of SiC in the silicon carbide is ≥90%, and the particle size is ≤5 mm.
[0053] All contents mentioned in this article are by mass percentage unless otherwise specified.
[0054] Example 1
[0055] A method for accurately controlling the oxygen content of low-carbon, low-silicon, high-sulfur steel comprises the following steps:
[0056] a. Converter smelting: The main raw material ratio of the converter is 87.6% molten iron, 10.4% scrap steel and 2.0% desulfurized slag iron. The sulfur in the desulfurized slag iron is recovered by using the converter oxidizing atmosphere. The converter adopts less slag smelting to make low basicity to keep sulfur and phosphorus. The converter slag material consumption is 29.0kg / t steel, and the final slag basicity R is 2.3. Not only can high-sulfur and phosphorus molten steel be obtained at the end of the converter, but the end S content is 0.037% and the end P content is 0.043%; on the other hand, the iron-containing material in the desulfurized slag iron can also be recovered, which brings the beneficial effect that the consumption of steel material at the end of the converter is reduced to 1057.0kg / t;
[0057] b. The final carbon retention steel tapping reduces the final oxidation, the final temperature is 1638℃, the final carbon is 0.074%, the final oxygen content is 345ppm, the final slag T·Fe content is 13.1%, and the final bottom blowing intensity is 0.11Nm 3 / min·t, strong stirring for 2min to promote further reaction of carbon and oxygen;
[0058] c. During the steel-discharging process, the ladle has a maximum flow rate of 1000NL / min. When 1 / 2 of the steel is discharged, 17.4kg / t of low-carbon ferromanganese, 6.86kg / t of high-sulfur ferrosulfur, and 0.30kg / t of ferrophosphorus are added in sequence; when 3 / 4 of the steel is discharged, 3.2kg / t of lime and 1.9kg / t of wollastonite are added;
[0059] d. According to the oxygen determination result of 125.6ppm at the argon station and the carbon retention at the end, the oxygen content at the argon station is 42.6ppm when 120m of aluminum wire is fed (the pure aluminum consumption per ton of steel is 0.214kg / t steel) is calculated according to Formula 1;
[0060] e. During the refining and heating process, a total of 1.23kg / t of lime, 1.47kg / t of wollastonite, and 0.92kg / t of raw dolomite were added in 4 times, with each addition amount being 1 / 4 of the total amount. The process electrode gear corresponding to each batch of materials was 10 gear → 8 gear → 6 gear → 4 gear. The added raw dolomite MgCO3=MgO+CO2 decomposition reaction can play the role of foaming agent and furnace protection agent. The MgO content in the refined slag is 7.3%, which can reduce the erosion of magnesia carbon bricks on the slag line;
[0061] f. After heating, add environmentally friendly aluminum-based reducing agent with a total amount of 0.83kg / t steel, lime with a total amount of 0.30kg / t steel, and wollastonite with a total amount of 0.37kg / t steel to the slag surface in small batches and multiple batches to make slag. The slag making materials are added in 3 batches, and the amount added each time is 1 / 3 of the total amount. The interval between each addition is 3 minutes. The argon blowing and stirring flow rate during the slag making process is controlled to be 500-800NL / min;
[0062] g. After slag making, the refined slag sample was taken. The slag basicity R was 1.9, and the mass percentage of T·Fe+MnO% was 8.3%. This can avoid the high content of T·Fe+MnO%, which causes the slag to continuously transfer oxygen to the molten steel, and can also better balance the dissolved oxygen content in the molten steel. The dissolved oxygen content at the end of refining was 56.2ppm.
[0063] h. According to Formula 2 and Formula 3, 105m of low-splash solid pure calcium cored wire needs to be fed to control the degree of denaturation γ Ca It is 0.292, and the soft blow is 14 minutes out of the station;
[0064] i. Continuous casting: After continuous casting, the ingot is lightly pressed down, with a total reduction of 15 mm. The light pressing devices 2, 3, 4, 5, and 6 are controlled, with reductions of 2 mm, 3 mm, 4 mm, 4 mm, and 2 mm respectively.
[0065] The C content of the ingot is 0.060%, the Si content is 0.0051%, the T·[O] total oxygen content is 130.9ppm, the Mn / S is 3.77, the terminal C and Si contents are low, the T·[O] total oxygen content is appropriate, the surface quality is good, and the spindle rate of sulfide inclusions with an aspect ratio of ≤4 is 81.4%.
[0066] Example 2
[0067] A method for accurately controlling the oxygen content of low-carbon, low-silicon, high-sulfur steel comprises the following steps:
[0068] a. The main raw material ratio of the furnace is 88.2% molten iron, 7.8% scrap steel and 4.0% desulfurized slag iron. The sulfur in the desulfurized slag iron is recovered by using the oxidizing atmosphere of the converter. The converter adopts less slag smelting to make low basicity to preserve sulfur and phosphorus. The converter slag material consumption is 27.3kg / t steel, and the final slag basicity R is 2.1. Not only can high-sulfur and phosphorus molten steel be obtained at the end of the converter, but the end S content is 0.048% and the end P content is 0.041%; on the other hand, the iron-containing material in the desulfurized slag iron can also be recovered, which brings the beneficial effect that the consumption of steel material at the end of the converter is reduced to 1042.9kg / t steel;
[0069] b. The final carbon retention steel tapping reduces the final oxidation, the final temperature is 1643℃, the final carbon is 0.072%, the final oxygen content is 359ppm, the final slag T·Fe content is 13.5%, and the final bottom blowing intensity is 0.12Nm 3 / min·t, strong stirring for 1.8min to promote further reaction of carbon and oxygen;
[0070] c. During the steel-tapping process, the ladle has a maximum flow rate of 900NL / min. When 1 / 2 of the steel is tapped, 17.5kg / t of low-carbon ferromanganese, 6.71kg / t of high-sulfur ferrosulphur, and 0.42kg / t of ferrophosphorus are added in sequence; when 3 / 4 of the steel is tapped, 3.3kg / t of lime and 1.8kg / t of wollastonite are added;
[0071] d. According to the oxygen determination result of 136.5ppm at the argon station and the carbon retention at the end, the oxygen content at the argon station is 48.3ppm when 140m of aluminum wire is fed (the pure aluminum consumption per ton of steel is 0.251kg / t steel) according to Formula 1;
[0072] e. During the refining and heating process, a total of 1.48kg / t of lime, 1.48kg / t of wollastonite, and 1.02kg / t of raw dolomite were added in 5 times, with each addition amount being 1 / 5 of the total amount. The process electrode gears corresponding to each batch of materials were 11 gears → 9 gears → 7 gears → 5 gears → 3 gears. The added raw dolomite MgCO3=MgO+CO2 decomposition reaction can play the role of foaming agent and furnace protection agent. The MgO content in the refined slag is 7.4%, which can reduce the erosion of magnesia carbon bricks on the slag line;
[0073] f. After heating, add environmentally friendly aluminum-based reducing agent with a total amount of 0.90kg / t steel, lime with a total amount of 0.37kg / t steel, and wollastonite with a total amount of 0.37kg / t steel to the slag surface in small batches and multiple batches to make slag. The slag making materials are added in 3 batches, and the amount added each time is 1 / 3 of the total amount. The interval between each addition is 3 minutes. The argon blowing and stirring flow rate during the slag making process is controlled to be 500-700NL / min;
[0074] g. After slag making, take the refined slag sample. The slag basicity R is 2.0, and the mass percentage of T·Fe+MnO% is 7.8%. This can avoid the high content of T·Fe+MnO%, which causes the slag to continuously transfer oxygen to the molten steel, and can also better balance the dissolved oxygen content in the molten steel. The dissolved oxygen content at the end of refining is controlled to be 53.8ppm after feeding the aluminum wire for 10m.
[0075] h. According to Formula 2 and Formula 3, 100m of low-splash solid pure calcium cored wire needs to be fed to control the degree of denaturation γ Ca It is 0.297, and the soft blow takes 13 minutes to exit the station;
[0076] i. Continuous casting: The ingot after continuous casting is lightly pressed down, with a total reduction of 15 mm. The light pressing devices 2, 3, 4, 5, and 6 are controlled, with reductions of 2 mm, 3 mm, 4 mm, 4 mm, and 2 mm respectively.
[0077] The C content of the ingot is 0.058%, the Si content is 0.0057%, the T·[O] total oxygen content is 128.0ppm, the Mn / S is 3.80, the terminal C and Si contents are low, the T·[O] total oxygen content is appropriate, the surface quality is good, and the spindle rate of sulfide inclusions with an aspect ratio of ≤4 is 81.9%.
[0078] Example 3
[0079] A method for accurately controlling the oxygen content of low-carbon, low-silicon, high-sulfur steel comprises the following steps:
[0080] a. The main raw material ratio of the converter is 89.1% molten iron, 4.9% scrap steel and 6.0% desulfurized slag iron. The sulfur in the desulfurized slag iron is recovered by using the oxidizing atmosphere of the converter. The converter adopts less slag smelting to make low basicity to preserve sulfur and phosphorus. The converter slag material consumption is 25.2kg / t steel, and the final slag basicity R is 2.2. Not only can high-sulfur and phosphorus molten steel be obtained at the end of the converter, but the end S content is 0.058% and the end P content is 0.039%; on the other hand, the iron-containing material in the desulfurized slag iron can also be recovered, which brings the beneficial effect that the consumption of steel material at the end of the converter is reduced to 1029.1kg / t steel;
[0081] b. The final carbon retention steel tapping reduces the final oxidation, the final temperature is 1635℃, the final carbon is 0.069%, the final oxygen content is 368ppm, the final slag T·Fe content is 13.8%, and the final bottom blowing intensity is 0.11Nm 3 / min·t, strong stirring for 2.0min to promote further reaction of carbon and oxygen;
[0082] c. During the steel-tapping process, the ladle has a maximum flow rate of 900NL / min. When 1 / 2 of the steel is tapped, 17.6kg / t of low-carbon ferromanganese, 6.35kg / t of high-sulfur ferrosulphur, and 0.39kg / t of ferrophosphorus are added in sequence; when 3 / 4 of the steel is tapped, 3.4kg / t of lime and 1.7kg / t of wollastonite are added;
[0083] d. According to the oxygen content of 141.5ppm at the argon station and the carbon retention at the end, 150m of aluminum wire was fed according to Formula 1 (the pure aluminum consumption per ton of steel is 0.271kg / t steel), and the oxygen content at the argon station was 53.7ppm;
[0084] e. During the refining and heating process, a total of 1.49kg / t of lime, 1.24kg / t of wollastonite, and 0.87kg / t of raw dolomite were added in 4 times, with each addition amount being 1 / 4 of the total amount. The process electrode gear corresponding to each batch of materials was 9th gear → 7th gear → 5th gear → 3rd gear. The added raw dolomite MgCO3=MgO+CO2 decomposition reaction can play the role of foaming agent and furnace protection agent. The MgO content in the refined slag is 7.2%, which can reduce the erosion of magnesia carbon bricks on the slag line;
[0085] f. After heating, add environmentally friendly aluminum-based reducing agent with a total amount of 0.97kg / t steel, lime with a total amount of 0.38kg / t steel, and wollastonite with a total amount of 0.31kg / t steel to the slag surface in small batches and multiple batches to make slag. The slag making materials are added in 3 batches, and the amount added each time is 1 / 3 of the total amount. The interval between each addition is 3 minutes. The argon blowing and stirring flow rate during the slag making process is controlled to be 600-800NL / min;
[0086] g. After slag making, take the refined slag sample, the slag basicity R is 2.1, T·Fe+MnO% mass percentage is 7.1%, which can avoid the high T·Fe+MnO% content, causing the slag to continuously transfer oxygen to the molten steel, and can better balance the dissolved oxygen content in the molten steel. The dissolved oxygen content at the end of refining is controlled to be 57.3ppm after feeding the aluminum wire for 15m;
[0087] h. According to Formula 2 and Formula 3, 110m of low-sputtering solid pure calcium cored wire needs to be fed to control the degree of denaturation γ Ca It is 0.288, soft blowing for 15 minutes to exit the station;
[0088] i. Continuous casting: The ingot after continuous casting is lightly pressed down, with a total reduction of 15 mm. The light pressing devices 2, 3, 4, 5, and 6 are controlled, with reductions of 2 mm, 3 mm, 4 mm, 4 mm, and 2 mm respectively.
[0089] The C content of the ingot is 0.059%, the Si content is 0.0053%, the T·[O] total oxygen content is 133.5ppm, the Mn / S is 3.75, the terminal C and Si contents are low, the T·[O] total oxygen content is appropriate, the surface quality is good, and the spindle rate of sulfide inclusions with an aspect ratio of ≤4 is 81.1%.
[0090] Comparative Example 1
[0091] The main raw material ratio of the converter is 85.9% molten iron and 14.1% scrap steel. The converter is smelted according to conventional low-carbon steel grades. The converter slag consumption is 49.6kg / t steel, and the final slag basicity R is 3.3; the final temperature is 1637℃, the final carbon content is 0.043%, the phosphorus content is 0.018%, the sulfur content is 0.019%, the oxygen content is 605ppm, the final slag T·Fe content is 16.8%, and the steel material consumption is 1070.4kg / t steel;
[0092] The amount of slag discharged from the converter is strictly controlled. During the steel-making process, 1.5kg / t of ferroaluminum, 18.8kg / t of low-carbon ferromanganese, 7.25kg / t of high-sulfur ferrosulfur, 1.32kg / t of ferrophosphorus, 1.8kg / t of lime, and 3.3kg / t of wollastonite are added in sequence. The argon station blows argon for 2 minutes, and the oxygen is set at 71.0ppm. The aluminum consumption converted from ferroaluminum during the steel-making process is 0.589kg / t of steel.
[0093] After LF enters the station, the temperature is raised to above 1580℃. After heating, lime and wollastonite are added in batches to make slag, and silicon carbide is added to the slag surface for diffusion deoxidation. The ability of silicon carbide to remove oxygen from the slag is relatively weak, and the diffusion deoxidation rate is slow. The high oxygen in the slag will continue to transfer oxygen to the molten steel. It is necessary to feed aluminum wire multiple times to reduce the oxygen content of the molten steel. Silicon carbide is easy to enter the molten steel during the slag making and stirring process, causing the molten steel to increase silicon and carbon. In this embodiment, the total amount of lime added during the slag making process is 1.25 kg / t steel, the total amount of wollastonite is 1.88kg / t steel, the total amount of silicon carbide is 1.13kg / t steel, the content of T·Fe+MnO in the slag at the end of refining is 23.1%, the slag basicity is R is 1.4, the MgO content in the slag is 7.0%, which is relatively high (refining slag is generally ≤5%) due to the corrosion and dissolution of the magnesia carbon bricks in the ladle slag line, the dissolved oxygen content at the end of refining is 73.8ppm, and the silicon content is 0.0238%, which exceeds the composition requirements of the low-carbon, low-silicon and high-sulfur steel;
[0094] After continuous casting, the billet is lightly pressed without any casting;
[0095] The C content of the ingot is 0.054%, the Si content is 0.0238%, the T·[O] total oxygen content is 158.8ppm, the Mn / S is 3.59, and the Si content is relatively high, which aggravates the wear of the tool during the cutting process and cannot meet the needs of mid-to-high-end customers. The T·[O] total oxygen content is relatively high, the overheating degree is high, the segregation is relatively serious, and the spindle rate of sulfide inclusions with an aspect ratio of ≤4 is only 50.8%.
[0096] Comparative Example 2
[0097] The main raw material ratio of the converter is 86.7% molten iron and 13.3% scrap steel. The converter is smelted according to conventional low-carbon steel grades. The converter slag consumption is 50.5kg / t steel, and the final slag basicity R is 3.4; the final temperature is 1645℃, the final carbon content is 0.039%, the sulfur content is 0.020%, the phosphorus content is 0.016%, the oxygen content is 667ppm, the final slag T·Fe content is 17.3%, and the steel material consumption is 1071.1kg / t steel;
[0098] The amount of slag discharged from the converter is strictly controlled. During the steel-making process, 1.7kg / t of ferroaluminum, 19.0kg / t of low-carbon ferromanganese, 7.12kg / t of high-sulfur ferrosulfur, 1.29kg / t of ferrophosphorus, 3.7kg / t of lime, and 1.2kg / t of wollastonite are added in sequence. The argon station blows argon for 2 minutes, and the oxygen is set at 68.2ppm. The aluminum consumption converted from ferroaluminum during the steel-making process is 0.681kg / t of steel.
[0099] After LF enters the station, the temperature is raised to above 1580℃. After heating, lime and wollastonite are added in batches to make slag, and silicon carbide is added to the slag surface for diffusion deoxidation. The ability of silicon carbide to remove oxygen from the slag is relatively weak, and the diffusion deoxidation rate is slow. The high oxygen in the slag will continue to transfer oxygen to the molten steel. It is necessary to feed aluminum wire multiple times to reduce the oxygen content of the molten steel. Silicon carbide is easy to enter the molten steel during the slag making and stirring process, causing the molten steel to increase silicon and carbon. In this embodiment, the total amount of lime added during the slag making process is 2.50 kg / t steel, the total amount of wollastonite is 1.25kg / t steel, the total amount of silicon carbide is 0.64kg / t steel, the content of T·Fe+MnO in the slag at the end of refining is 4.6%, the slag basicity is R is 2.6, the MgO content in the slag is 6.8%, which is relatively high (refining slag is generally ≤5%) due to the corrosion and dissolution of the magnesia carbon bricks in the ladle slag line, the dissolved oxygen content at the end of refining is 38.5ppm, and the silicon content is 0.0186%, which exceeds the composition requirements of the low-carbon, low-silicon and high-sulfur steel;
[0100] After continuous casting, the billet is lightly pressed without any casting;
[0101] The C content of the ingot is 0.048%, the Si content is 0.0186%, the T·[O] total oxygen content is 93.5ppm, and the Mn / S is 3.57. The Si content is relatively high, which aggravates the wear of the tool during the cutting process and cannot meet the needs of mid-to-high-end customers. The T·[O] total oxygen content is relatively low, the overheating degree is high, the segregation is relatively serious, and the spindle rate of sulfide inclusions with an aspect ratio of ≤4 is only 48.7%.
[0102] Comparative Example 3
[0103] Referring to Example 2, the following steps are included:
[0104] a. The main raw material ratio of the converter is 88.0% molten iron, 8.0% scrap steel and 4.0% desulfurized slag iron. The sulfur in the desulfurized slag iron is recovered by using the oxidizing atmosphere of the converter. The converter adopts less slag smelting to make low basicity to retain sulfur and phosphorus. The converter slag consumption is 26.8kg / t steel, and the final slag basicity R is 2.3. High sulfur and phosphorus molten steel is obtained at the end of the converter, and the final S content is 0.043%, and the final P content is 0.045%;
[0105] b. The final carbon retention steel tapping reduces the final oxidation, the final temperature is 1641℃, the final carbon is 0.079%, the final oxygen content is 316ppm, the final slag T·Fe content is 12.1%, and the final bottom blowing intensity is 0.11Nm 3 / min·t, strong stirring for 2.0min to promote further reaction of carbon and oxygen;
[0106] c. During the steel-tapping process, the ladle has a maximum flow rate of 950NL / min. When the steel is 1 / 2 tapped, 17.4kg / t of low-carbon ferromanganese, 6.86kg / t of high-sulfur ferrosulfur, and 0.22kg / t of ferrophosphorus are added in sequence; when the steel is 3 / 4 tapped, 3.2kg / t of lime and 1.8kg / t of wollastonite are added;
[0107] d. The oxygen content at the argon station is not fixed. According to the field operation experience, 120m of aluminum wire is fed (the pure aluminum consumption per ton of steel is 0.215kg / t steel), and the oxygen content at the argon station is 23.5ppm. The oxygen content of the molten steel is low, which is not conducive to the accurate dissolved oxygen content of the molten steel in the refining process.
[0108] e. During the refining and heating process, a total of 1.33kg / t of lime, 1.44kg / t of wollastonite, and 0.93kg / t of raw dolomite were added in 4 times, with each addition amount being 1 / 4 of the total amount. The process electrode gear corresponding to each batch of materials was 10 gear → 8 gear → 6 gear → 4 gear. The added raw dolomite MgCO3=MgO+CO2 decomposition reaction can play the role of foaming agent and furnace protection agent. The MgO content in the refined slag is 7.1%, which can reduce the erosion of magnesia carbon bricks on the slag line;
[0109] f. After heating, add lime with a total amount of 0.32kg / t steel and wollastonite with a total amount of 0.36kg / t steel to the slag surface in small batches and multiple batches to make slag. The slag making materials are added in 3 batches, and the amount added each time is 1 / 3 of the total amount. The interval between each addition is 3 minutes. The argon blowing and stirring flow rate during the slag making process is controlled to be 600-800NL / min;
[0110] g. After slag making, a refined slag sample was taken. The slag basicity R was 2.1, and the mass percentage of T·Fe+MnO% was 5.8%. The T·Fe+MnO% content of the refined slag was low, resulting in a low dissolved oxygen content in equilibrium with the molten steel. 0.467kg / t of iron oxide scale was added to the slag surface to increase oxygen in the molten steel. The argon blowing stirring flow rate was controlled at 300-500NL / min and stirred for 8 minutes. The dissolved oxygen content at the end of refining was 46.8ppm, which was low.
[0111] h. According to Formula 2 and Formula 3, 70m of low-splash solid pure calcium cored wire needs to be fed to control the degree of denaturation γ Ca The value is 0.191, soft blowing 12min out of the station; sulfide denaturation degree γ Ca The value is low, and the sulfide is not completely denatured;
[0112] i. Continuous casting: After continuous casting, the ingot is lightly pressed down, with a total reduction of 15 mm. The light pressing devices 2, 3, 4, 5, and 6 are controlled, with reductions of 2 mm, 3 mm, 4 mm, 4 mm, and 2 mm respectively.
[0113] The C content of the ingot is 0.065%, the Si content is 0.0054%, the T·[O] total oxygen content is 119.2ppm, the Mn / S is 3.73, the end point C, Si content is low, the T·[O] total oxygen content is low, the surface quality is good, and the sulfide modification degree is γ Ca The spindle rate of sulfide inclusions with an aspect ratio of ≤4 is 70.8%.
[0114] Comparative Example 4
[0115] Referring to Example 2, the following steps are included:
[0116] a. The main raw material ratio of the converter is 88.5% molten iron, 7.5% scrap steel and 4.0% desulfurized slag iron. The sulfur in the desulfurized slag iron is recovered by using the oxidizing atmosphere of the converter. The converter adopts less slag smelting to make low basicity to retain sulfur and phosphorus. The converter slag consumption is 28.4kg / t steel, and the final slag basicity R is 2.2. High sulfur and phosphorus molten steel is obtained at the end of the converter, and the final S content is 0.051% and the final P content is 0.035%;
[0117] b. The converter failed to retain carbon at the end, the end temperature was 1647℃, the end carbon content was 0.041%, the end oxygen content was 644ppm, the final slag T·Fe content was 17.1%, and the end bottom blowing intensity was 0.10Nm 3 / min·t, strong stirring for 2.0min to promote further reaction of carbon and oxygen;
[0118] c. During the steel-tapping process, the ladle has a maximum flow rate of 900NL / min. When 1 / 2 of the steel is tapped, 18.7kg / t of low-carbon ferromanganese, 6.58kg / t of high-sulfur ferrosulphur, and 0.60kg / t of ferrophosphorus are added in sequence; when 3 / 4 of the steel is tapped, 3.4kg / t of lime and 1.6kg / t of wollastonite are added;
[0119] d. The oxygen content at the argon station is not fixed. According to the field operation experience, 150m of aluminum wire is fed (the pure aluminum consumption per ton of steel is 0.270kg / t steel), and the oxygen content at the argon station is 90.4ppm. The oxygen content of the molten steel is too high, which is not conducive to the accurate dissolved oxygen content of the molten steel in the refining process.
[0120] e. During the refining and heating process, a total of 1.40kg / t of lime, 1.30kg / t of wollastonite, and 1.1kg / t of raw dolomite were added in 4 times, with each addition amount being 1 / 4 of the total amount. The process electrode gear corresponding to each batch of materials was 9th gear → 7th gear → 5th gear → 3rd gear. The added raw dolomite MgCO3=MgO+CO2 decomposition reaction can play the role of foaming agent and furnace protection agent. The MgO content in the refined slag is 7.5%, which can reduce the erosion of magnesia carbon bricks on the slag line;
[0121] f. After heating, add environmentally friendly aluminum-based reducing agent with a total amount of 0.98kg / t steel, lime with a total amount of 0.33kg / t steel, and wollastonite with a total amount of 0.46kg / t steel to the slag surface in small batches and multiple batches to make slag. The slag making materials are added in 3 batches, and the amount added each time is 1 / 3 of the total amount. The interval between each addition is 3 minutes. The argon blowing and stirring flow rate during the slag making process is controlled to be 600-800NL / min;
[0122] g. After slag making, the refined slag sample was taken. The slag basicity R was 1.8, and the mass percentage of T·Fe+MnO% was 10.1%. The T·Fe+MnO% content of the refined slag was high, causing the slag to continuously transfer oxygen to the molten steel. The dissolved oxygen content at the refining endpoint was controlled to be 64.2ppm by feeding the aluminum wire for 65m, which was high;
[0123] h. According to Formula 2 and Formula 3, 150m of low-splash solid pure calcium cored wire needs to be fed to control the degree of denaturation γ Ca It is 0.409, soft blowing for 12 minutes to exit the station;
[0124] i. Continuous casting: The ingot after continuous casting is lightly pressed down, with a total reduction of 15 mm. The light pressing devices 2, 3, 4, 5, and 6 are controlled, with reductions of 2 mm, 3 mm, 4 mm, 4 mm, and 2 mm respectively.
[0125] The C content of the ingot is 0.047%, the Si content is 0.0048%, the T·[O] total oxygen content is 141.1ppm, the Mn / S is 3.80, the end point C and Si content are low, the T·[O] total oxygen content is high, the surface quality is good, and the sulfide modification degree is γ Ca The spindle rate of sulfide inclusions with an aspect ratio of ≤4 is 81.2%.
[0126] In summary, the dissolved oxygen content [O] of the molten steel at the refining endpoint of Examples 1, 2, and 3 of the present invention is precisely controlled at 50-60 ppm, the total oxygen content T·[O] of the ingot is precisely controlled at 125-135 ppm, the oxygen content in the steel is appropriate, and the spindle rate of sulfide inclusions with an aspect ratio of ≤4 is above 80%, which is 27.6%, 28.1%, and 27.3% higher than the average of the comparative example, respectively, improving the morphology and distribution of sulfides and improving the cutting performance of the product;
[0127] In embodiments 1, 2 and 3 of the present invention, desulfurized slag iron is recovered by a converter, and a low-slag smelting and low-basicity slag process is used to obtain high-sulfur and phosphorus molten steel. The high-sulfur ferrosulphur is reduced by 0.33kg / t, 0.48kg / t and 0.84kg / t, respectively, compared with the average values of comparative examples 1 and 2, and the ferrophosphorus is reduced by 1.01kg / t, 0.89kg / t and 0.92kg / t, respectively, compared with the average values of comparative examples 1 and 2, and the alloy consumption is reduced. Another beneficial effect is that the metallic iron in the desulfurized slag iron can be recovered at the same time. The slag, the converter steel material consumption is reduced by 13.8kg / t, 27.8kg / t and 41.7kg / t, respectively, compared with the average values of comparative examples 1 and 2, and the slag material consumption is reduced by 21.1kg / t, 22.8kg / t and 24.9kg / t, respectively, compared with the average values of comparative examples 1 and 2.
[0128] In embodiments 1, 2 and 3 of the present invention, carbon is retained in the converter to tap steel, thereby reducing the terminal oxidizability, and the terminal oxygen content is between 300 and 400 ppm. Large flow bottom blowing, strong stirring and step-by-step weak deoxidation during the tapping process are used, and the deoxidation aluminum consumption is reduced by 0.42 kg / t steel, 0.38 kg / t steel and 0.36 kg / t steel, respectively, compared with the average values of comparative examples 1 and 2;
[0129] The oxygen removal capacity of Examples 1, 2 and 3 of the present invention is stronger than that of silicon carbide in the comparative example by using an environmentally friendly aluminum-based refining agent, and oxygen in the slag can be quickly removed, oxygen balance between slag and steel can be achieved, the oxygen content of molten steel can be accurately controlled, and silicon carbide can be avoided from increasing silicon and carbon. The Si content of the embodiments is 0.0051%, 0.0057% and 0.0053%, respectively, which are all lower than 0.010%, and are respectively reduced by more than 0.015% compared with the Si content of the comparative example, which can effectively avoid the formation of silicate hard inclusions due to high Si content and reduce the wear of the tool during the cutting process. The refining time of Examples 1, 2 and 3 is reduced by 17min, 20min and 15min respectively compared with the average value of Comparative Examples 1 and 2;
[0130] Examples 1, 2 and 3 of the present invention use raw dolomite as a foaming agent and a furnace protection agent to reduce the melting loss of magnesia carbon bricks at the ladle slag line. Compared with the average values of comparative examples 1 and 2, the erosion of the slag line is reduced by 0.43 kg / t, 0.46 kg / t and 0.45 kg / t respectively.
[0131] Embodiments 1, 2 and 3 of the present invention adopt low superheat casting and light reduction technology of the ingot to accurately control the reduction amount, squeeze out the bubbling oxygen adsorbed on the surface of the ingot during the solidification process, obtain high-quality ingots with good surface quality and less segregation, and improve the cutting performance of the product.
[0132] Comparative Example 3, referring to Example 2, the argon station was not accurately fed with oxygen at the inlet, and the argon station fed more aluminum wire according to operating experience, resulting in an oxygen content of 23.5ppm at the outlet of the argon station, and a content of 5.8% of T·Fe+MnO% in the refined slag, resulting in a low dissolved oxygen content in equilibrium with the molten steel. It was necessary to add 0.467kg / t of iron oxide scale to the slag surface, and extend the stirring time by 8min to promote the transfer of oxygen from the iron oxide scale to the molten steel. The dissolved oxygen content at the end of refining was 46.8ppm, and the total oxygen content of the ingot T·[O] was 119.2ppm. The dissolved oxygen content of the molten steel and the total oxygen content of the ingot were low; 70m of low-sputtering solid pure calcium cored wire was fed to control the degree of modification γ Ca The value is 0.191, and the sulfide denaturation degree γ Ca The value is low, the sulfide is not completely denatured, and the spindle rate of sulfide inclusions with an aspect ratio of ≤4 is 70.8%;
[0133] Comparative Example 4, referring to Example 2, the argon station was not accurately fed with oxygen. The argon station fed less aluminum wire according to operating experience, resulting in an oxygen content of 90.4ppm at the argon station outlet, and a content of 10.1% T·Fe+MnO% in the refining slag, resulting in a high dissolved oxygen content in equilibrium with the molten steel. It was necessary to feed 65m of aluminum wire to reduce the dissolved oxygen content at the end of refining. The dissolved oxygen content at the end of refining was 64.2ppm, and the total oxygen content of the ingot T·[O] was 141.1ppm. The dissolved oxygen content of the molten steel and the total oxygen content of the ingot were high. 150m of low-sputtering solid pure calcium cored wire was fed, and the amount of calcium wire fed was too much to control the degree of modification. Ca The value is 0.409, and the sulfide denaturation degree γ Ca The value is high, and the spindle rate of sulfide inclusions with an aspect ratio of ≤4 is 81.2%. The spindle rate does not increase with the high degree of denaturation γ Ca As the calcium line increases, it continues to increase, resulting in excessive cost waste.
[0134] Table 1 Parameters of main raw materials, final molten steel and slag in converter smelting
[0135]
[0136]
[0137] Table 2 Converter steel charging and argon station molten steel parameters
[0138]
[0139]
[0140] Table 3 LF refining feed and related parameters
[0141]
[0142]
[0143] Table 4 Composition of slag sample at the end of LF refining
[0144]
[0145]
[0146] Table 5 Chemical composition control of ingot
[0147]
[0148]
[0149] Note: [O] is the mass percentage of dissolved oxygen at the end point of LF refining; the sulfide inclusion spindle rate is the result of electron microscope inspection, which refers to the ratio of spindle-shaped sulfides with a sulfide inclusion length / width ratio of ≤4. The higher the sulfide spindle rate in the steel, the better the turning performance of the steel.
[0150] Table 6 Continuous casting related control parameters
[0151]
[0152] The detailed description of a method for accurately controlling the oxygen content of a low-carbon, low-silicon, high-sulfur steel with reference to the above-mentioned embodiment is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for accurately controlling the oxygen content of low-carbon, low-silicon, high-sulfur steel, characterized in that: The following steps are involved: a. Converter smelting: put in molten iron, desulfurized slag and scrap steel for smelting; the basicity of converter final slag is controlled at 2.0-2.5; phosphorus and sulfur are not removed; b. Carbon is retained and steel is tapped at the end of the converter, and argon is blown from the bottom for strong stirring; c. The converter tapping process adopts a step-by-step weak deoxidation process. When the steel is tapped 1 / 2, low-carbon ferromanganese with a mass percentage of C ≤ 0.2%, high-sulfur ferrosulphur and ferrophosphorus alloy with a mass percentage of S of 50-55% are added in sequence. When the steel is tapped 3 / 4, lime and wollastonite are added. The slag is blocked by a slide plate to control the slag amount of the converter to ≤ 3kg / t. d. Temperature measurement and oxygen determination at the argon blowing station. The dissolved oxygen content w[O] is determined by the argon blowing station. Ar Results: Precise feeding of aluminum wire. After feeding aluminum wire, the dissolved oxygen content of molten steel was controlled to be 30-80ppm. The feeding amount of aluminum wire was l Al for: Among them, m st is the weight of molten steel, in t; η is the empirical parameter of aluminum wire deoxidation efficiency, when the converter end point C≥0.060%, η is 1.15~1.25; when the converter end point C<0.060%, η is 1.25~1.45; ρ Al is the density of aluminum, in kg / m 3 ; d is the diameter of the aluminum wire, in m; w Al is the mass percentage of aluminum in the aluminum wire, %; l Al The unit is m; w[O] Ar The unit is ppm; e. The LF station is heated, and lime, raw dolomite and wollastonite are added in batches during the heating process; f. After the heating is completed, an aluminum-based reducing agent is added to diffuse and deoxidize the slag surface, and lime and wollastonite are added to make slag; g. After slag making, alloy fine-tuning, aluminum wire feeding or iron oxide scale addition on the slag surface are performed to control the final dissolved oxygen content of the molten steel to 45-65ppm; h. LF is heated up twice. After the heating is completed, pure calcium cored wire is fed in to denature the sulfide inclusions. After the wire is fed, it is soft blown out of the station; i. Continuous casting: The ingot after continuous casting is lightly pressed down; The weight percentages of carbon, silicon and sulfur in the low-carbon, low-silicon and high-sulfur steel are respectively: C≤0.090%, Si≤0.010%, and S0.30-0.50%.
2. The method for accurately controlling the oxygen content of low-carbon, low-silicon, high-sulfur steel according to claim 1 is characterized in that: In step a, the mass percentage of molten iron is 83-93%, the mass percentage of desulfurized slag iron is 2-6%, and the rest is scrap steel; the S content at the converter end point is 0.030-0.060%, and the P content is 0.035-0.045%.
3. The method for accurately controlling the oxygen content of low-carbon, low-silicon, high-sulfur steel according to claim 1 is characterized in that: In step b, the mass percentage of carbon at the converter end point is 0.060-0.080%, the mass percentage of oxygen at the converter end point is 300-400 ppm, the end point temperature is 1620-1660°C; the argon flow rate at the converter end point is 0.10-0.12 Nm 3 / min·t, stirring for 1.5 to 2.5 minutes.
4. The method for accurately controlling oxygen content in low-carbon, low-silicon, high-sulfur steel according to claim 1, characterized in that: In step c, the addition amounts of low carbon ferromanganese, high sulfur ferrosulfur and ferrophosphorus alloy are 17.5±0.2kg / t steel, 22.3*(w[S] CC -w[S] BOF )±0.05kg / t steel, 39.7*(w[P] CC -w[P] BOF )±0.05kg / t steel, where w[S] CC , w[P] CC are the target values of the mass percentage of sulfur and phosphorus in the finished product, w[S] BOF , w[P] BOF They are the mass percentages of sulfur and phosphorus at the converter end point respectively; the amounts of lime and wollastonite added are 3.0-3.5kg / t steel and 1.5-2.0kg / t steel respectively.
5. The method for accurately controlling oxygen content in low-carbon, low-silicon, high-sulfur steel according to claim 1, characterized in that: In step c, the mass percentage of each component in low-carbon ferromanganese is: Mn 85-90%, C≤0.2%, Si≤0.5%; the mass percentage of each component in high-sulfur ferrosulphur is: S 50-55%, C≤0.1%, Si≤0.5%; the mass percentage of each component in ferrophosphorus is: P 26-30%, C≤0.1%, Si≤0.5%.
6. The method for accurately controlling oxygen content in low-carbon, low-silicon, high-sulfur steel according to claim 1, characterized in that: In step e, the added amounts of lime, raw dolomite and wollastonite are 0.6-1.6 kg / t steel, 0.8-1.2 kg / t steel and 1.0-2.0 kg / t steel respectively, and they are added in 4-5 batches.
7. The method for accurately controlling oxygen content in low-carbon, low-silicon, high-sulfur steel according to claim 1 is characterized in that: In step f, a total amount of 0.6-1.0 kg / t steel of an environmentally friendly aluminum-based reducing agent, 0.2-0.4 kg / t steel of lime and 0.3-0.8 kg / t steel of wollastonite are added in small batches of 3-5 batches; the target composition of the refined slag is as follows by mass percentage: CaO 43-48%, SiO2 22-27%, Al2O3 14-16%, MgO 6-8%, T·Fe+MnO 6-10%, and the basicity CaO / SiO2 is 1.6-2.2; in the environmentally friendly aluminum-based reducing agent, the metal Al content is 18-22%, the Al2O3 content is 20-30%, the CaO content is 25-45%, the SiO2 content is ≤5%, the particle size is 5-30 mm, and the density is 2.3-2.7 kg / cm 3 .
8. The method for accurately controlling oxygen content in low-carbon, low-silicon, high-sulfur steel according to claim 1, characterized in that: In step g, feeding 0.075 m / t steel of aluminum wire can reduce 10 ppm of dissolved oxygen; adding 0.227 kg / t steel of iron oxide scale to the slag surface can increase 10 ppm of dissolved oxygen.
9. The method for accurately controlling oxygen content in low-carbon, low-silicon, high-sulfur steel according to claim 1, characterized in that: In step h, the sulfide morphology and composition are determined by the parameter of the modification reaction degree γ Ca Take control: Wherein, w[Ca] is the percentage of calcium in molten steel, in %; w[O] is the percentage of dissolved oxygen in molten steel, in %; w[S] is the percentage of sulfur in molten steel, in %; γ Ca The control range is 0.2~0.4; After feeding the line, soft blow for 10 to 15 minutes before leaving the station.
10. The method for accurately controlling oxygen content in low-carbon, low-silicon, high-sulfur steel according to claim 1, characterized in that: In step i, the total amount of light pressing is 10-20 mm, and the light pressing devices 2, 3, 4, 5, and 6 are controlled, with the amounts of pressing being 1-3 mm, 2-4 mm, 3-5 mm, 3-5 mm, and 1-3 mm, respectively.
11. The method for accurately controlling oxygen content in low-carbon, low-silicon, high-sulfur steel according to any one of claims 1 to 10, characterized in that: The low-carbon, low-silicon and high-sulfur steel includes the following chemical components in weight percentage: C≤0.090%, Si≤0.010%, S0.30-0.50%, P: 0.040-0.080%, T·[O]0.010%-0.015%, dissolved [O]0.0040%-0.0070%, Alt≤0.0050%, Mn / S 3-5, and the rest is Fe and unavoidable impurities.
Citation Information
Patent Citations
Smelting method for controlling oxygen content in steel casting blank
CN111154948A
Sulfur-containing free-cutting steel refining oxygen control method
CN117126984A
High-oxygen high-sulfur free-cutting steel 1215MS and oxygen-controlled LF smelting method thereof
CN117403147A
smelting process for low-carbon ultra-low-sulfur steel
DE102015113412A1
Process for smelting ultra-low-carbon and ultra-low-sulfur steel
WO2020215688A1
Cited By
Molten steel LF refining slagging method
CN122256602A
